INDEX-BASED JOIN IN MAPREDUCE USING HADOOP MAPFILES - Al Badarneh, Amer; Al-Rudaini, Mohammed; Ali, Faisal; Najadat, Hassan (MATTER: International Journal of Science and Technology, 2016)
Map Reduce stays an important method that deals with semi-structured or unstructured big data files, however, querying data mostly needs a Join procedure to accumulate the desired result from multiple huge files. Indexing in another hand, remains the best way to ease the access to a specific record(s) in a timely manner. In this paper, the authors are investigating the performance gain by implementing Map File indexing and Join algorithms together.